Future scientific potential personnel in education interdisciplinary integration and from dependence of use efficient methods (Multidisciplinary Journal of Science and Technology, 2024)
In our republic Third Renaissance to the period foundation being created present in the circumstances education system quality in terms of national and foreign experience harmonized international to standards suitable way new to stage raise according to wide comprehensive reforms done increase for defined priority assignments done increase on the way the most important from tasks one continuously education system teaching in the process interdisciplinary integration to the road to put of possibilities efficient to use efficient organize of reaching modern technologies done is to increase . Especially our country the world to the community by joining managed to one at the time competitive personnel issue very important to the topic turning around has managed